Hubungan antara Testimoni Produk, Kepercayaan, dan Keputusan Pembelian Online: Studi Empiris pada Mahasiswa Manajemen FEB Universitas Halu Oleo Kendari - Azis Muthalib, Dzulfikri (LP3M, Universitas Muhammadiyah Kendari, 2025)
This study aims to explain the effect of product testimonials on online purchase decisions, with trust as a mediating variable. This research is important because there is still limited evidence on how testimonials influence trust and purchase decisions among Management students at Halu Oleo University, Kendari. Data were collected from 90 Management students who had made online purchases in 2024 using purposive sampling. The analysis employed Structural Equation Modeling based on Partial Least Squares (SEM-PLS), which is appropriate for testing mediation models. The results show that product testimonials have a positive and significant effect on trust and also directly exert a positive and significant influence on online purchase decisions. Trust is proven to significantly affect purchase decisions and partially mediates the relationship between testimonials and purchase decisions. These findings indicate that good and authentic testimonials can enhance consumer trust and encourage online purchase decisions. E-commerce practitioners are advised to manage testimonials honestly and attractively to increase customer trust and boost sales.